Caracterização microestrutural, mecânica e eletroquímica de ligas Ti-35Nb-xY, com potencial aplicação biomédica - Barreto, Brendon Costa (2023)
Due to their peculiar properties, β-type Ti alloys have attracted notable interest for applications in several types of biomaterials, especially when compared with the properties of α and α+β type alloys. However, interdisciplinary efforts are still needed to promote the continuous search for materials that jointly have high resistance to corrosion in the body fluid, minimal release of metal ions harmful to the human body and bioactivity between the surrounding tissues and the biomaterial. Optimizing the composition of the alloy appears as an alternative and, in view of this, Nb is a promising element, due to its effectiveness in stabilizing the β phase, which has the lowest modulus of elasticity, by providing the TiO2 oxide film with greater resistance to corrosion. corrosion in simulated body fluids, as well as being non-toxic and non-allergenic. For this system, an ideal composition that integrates all the required properties has not yet been found. In view of this, Y, which is a rare earth element, gained prominence to be added to Ti, since it promotes the formation of Y2O3 and α-Y particles when reacting with interstitial oxygen and due to the effect of solute segregation, respectively. Such particles are correlated with microstructural refinement, oxide dispersion reinforcement and precipitation reinforcement, cell growth and greater stability to the protective oxide film. However, it is still necessary to understand in detail the relationship of Y additions in the Ti-35Nb system and its effects on phase formation, mechanical properties and corrosion resistance. Therefore, Ti-35Nb alloys were developed with the addition of 0.15%, 0.35% and 0.55% of Y (% by mass) in as-cast conditions and cooled in an oven after homogenization, highlighting the analogy between microstructure and properties. The results reveal that the additions of Y in the as-cast alloys promote the distribution of Y2O3 inside and at the grain boundaries, providing significant grain refinement and reduction in hardness. In furnace-cooled alloys, additions of Y promote the formation of Y2O3, ω and the formation of a eutectoid (α-Ti+α-Y) is suggested. In these alloys, the ω phase was mainly responsible for increasing hardness and modulus of elasticity. The addition of Y and heat treatment did not significantly influence the corrosion resistance of the alloys.